Immunomodulatory effects in the spleen‐injured mice following exposure to titanium dioxide nanoparticles. Issue 10 (16th November 2013) - Sang, Xuezi; Fei, Min; Sheng, Lei; Zhao, Xiaoyang; Yu, Xiaohong; Hong, Jie; Ze, Yuguan; Gui, Suxin; Sun, Qingqing; Ze, Xiao; Wang, Ling; Hong, Fashui
Abstract Immune injuries following the exposure of titanium dioxide nanoparticles (TiO2 NPs) have been greatly concerned along with the TiO2 NPs are widely used in pharmacology and daily life. However, very little is known about the immunomodulatory mechanisms in the spleen‐injured mice due to TiO2 NPs exposure. In this study, mice were continuously exposed to 2.5, 5, or 10 TiO2 NPs mg kg−1 body weight for 90 days with intragastric administration to investigate the immunomodulatory mechanisms in the spleen. The findings showed that TiO2 NPs exposure resulted in significant increases in spleen and thymus indices, and titanium accumulation, in turn led to histopathological changes and splenocyte apoptosis. Furthermore, the exposure of TiO2 NPs could significantly increase the levels of macrophage inflammatory protein (MIP)−1α, MIP‐2, Eotaxin, monocyte chemotactic protein‐1, interferon‐γ, vascular cell adhesion molecule‐1, interleukin‐13, interferon‐γ‐inducible protein‐10, migration inhibitory factor, CD69, major histocompatibility complex, protein tyrosine phosphatase, protein tyrosine kinase 1, basic fibroblast growth factor, Fasl, and GzmB expression, whereas markedly decrease the levels of NKG2D, NKp46, 2B4 expression involved in immune responses, lymphocyte healing and apoptosis. These findings would better understand toxicological effects induced by TiO2 NPs exposure. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 3562–3572, 2014.